The Correlation between demographic characteristics, emotional intelligence and conflict management strategies in managers of different organizational levels in hospitals affiliated to Tehran University of Medical Sciences - Seyed Hadi Hosseini; Mohammad Hadi Mousavi; Mostafa Esmaeili (Tehran University of Medical Sciences, 2021)
Introduction: Hospitals have conflicts because of their complex nature, so they need managers with high emotional intelligence for effective conflict management. There are contradictory results in the correlations between demographic characteristics, emotional intelligence and conflict management; therefore, this study was conducted to investigate the correlation between them in different managerial levels of the hospitals. Material & Methods: This analytical observational study was conducted on 100 senior and middle level managers (samples) of 8 selected hospitals affiliated to Tehran University of Medical Sciences in 2019.  We used a three-part questionnaire: Demographic characteristics, Emotional intelligence and Conflict management strategies, to collect data. SPSS 20 and statistical correlation tests including Pearson, t-test and analysis of variance were used for data analysis. Findings: There was a significant direct relationship between the mean score of emotional intelligence and its domains with problem-solving strategy (P <0.001). Also, statistically significant correlations were observed between age, marital status, major, organizational position, and work experience in a managerial position with emotional intelligence (P <0.05). In addition, there was a direct and statistically significant relationship between avoiding and problem-solving strategies with age and work experience, respectively (P <0.05). Discussion& Conclusion: It is necessary to take appropriate action to raise emotional intelligence and improve conflict management in hospitals, and according to the significant and direct relationships that observed, we can pay attention to select relevant managers for the hospitals.